Prevalence and factors associated with internet addiction among adolescents in Malaysia: a cross-sectional study - Chor, Yau Ooi; Ching, Siew Mooi; Ali, Norsiah; Sidek, Shahnul Kamal; Amat, Azlin; Yatim, Yusnita; Yahaya, Zaiton; Shamsuddin, Nabihah; Ibrahim, Idora; Abdul Majid, Fauzia; Othman, Fazlin Suhana; Zakaria, Nik Suhaila; et al. (Indian Association for Child and Adolescent Mental Health, 2020)
Introduction: Internet is important to university students, especially for medical students who use it to search for literature and relevant information. However, some of the users are experiencing a gradual loss of the ability to reduce the duration and frequency of their internet activities, despite the negative consequences. The literature on internet usage among Malaysian medical students is limited. This study aims to determine the prevalence and factors associated with internet usage among medical students in a public university in Malaysia. Methods: This cross-sectional study was performed among all the medical students (Year 1-5). Students were assessed on their internet activities using the internet addiction questionnaires (IAT). A Multiple Logistic Regression was used for data analysis. Results: The study was conducted among 426 students. The study population consisted of 156 males (36.6%) and 270 females (63.4%). The mean age was 21.6 ±1.5 years. Ethnicity distribution among the students was: Malays (55.6%), Chinese (34.7%), Indians (7.3%) and others (2.3%). According to the IAT, 36.9% of the study sample was addicted to the internet. Using the multivariate logistic regression analysis, we have found that the use of internet access for entertainment purposes (odds ratio [OR] 3.5, 95% confidence interval [CI] 1.05-12.00), male students (OR 1.8, 95% CI 1.01-3.21) and increasing frequency of internet usage were associated with internet addiction (OR 1.4, 95% CI 1.09- 1.67). Conclusion: Internet addiction is a relatively frequent phenomenon among medical students. The predictors of internet addiction were male students using it for surfing and entertainment purposes.